Mobile-assisted language learning and reading skill at Belisario Quevedo school - Heredia Caisa, Narcisa Yolanda (2023)
The research project aimed at determining the relationship between Mobile Device-Assisted Language Learning (MALL) and reading skills in seventh grade students at Belisario Quevedo School. The main objective was to develop reading skills, through the use of mobile devices and online pages such as Liveworksheets, the Wallpaper tool, and the WhatsApp application. The study was carried out under the Quali-Quantitative method, involving the quasi-experimental design because the evaluation instruments were used to obtain qualitative-quantitative results. In addition, two groups from the institution were selected, 34 students belonged to the control group and 34 were part of the experimental group, to whom a pre-evaluation and a post-evaluation were applied before and after the use of the proposal.